Analisis Maqashid Syariah Terhadap Hukum Mengambil Upah dari Penyedia Donor Darah: Studi Kasus Kota Tebing Tinggi - Anggit Aji Permana; Iwan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Wages are the rights of workers/laborers that are received and expressed in the form of money as compensation for a job. The context of taking wages in this research is a volunteer who finds a blood donor for a recipient in need, and from the results of his work the volunteer takes his wages from the donor as a form of remuneration for the results of his work. This statement raises the question of what the Maqashid Sharia views on the law of taking wages from blood donor providers. The purpose of this research is to find out the law on taking wages from blood donor providers using Maqoshid sharia. The research method used in this research is an empirical juridical research method, in this case the researcher conducted interviews which were carried out around the Seivani Hospital on Jl. Prof. M. Yamin No. 17, Rambutan District, Tebing Tinggi City. The research results obtained by Maqasid syari'ah mean the purpose of Allah and His Messenger in formulating Islamic laws. Taking and receiving wages is included in muamalah. however, based on the maqashid of the sharia, it can refer to the provisions of dharuriyat al khams, namely Al-Din (Maintaining Religion), Al Nafs (Maintaining Mental Health), Al-Aql (Maintaining Intellect), Al-Nasb (Guarding offspring) and Al-Mal (Guarding Property). In this research, what is emphasized more is referring to hifz al mal (maintenance of property). The concept of hifz al malIf this is related to the issue of determining and receiving wages from work results, there must be no elements that can eliminate workers' rights without reasons that are not justified by law, both positive law and sharia law. Because if If this is done, part of the volunteer's rights which he should have obtained from the results of the work he has done will be lost.